Service access experiences of immigrant and refugee caregivers of autistic children in Canada: A scoping review. - Lina Marie Casale; Stephen J Gentles; Janet McLaughlin; Margaret Schneider (PLoS ONE, 2023)
Primary caregivers are the main mediators of care for children with an autism diagnosis in Canada, and the navigation process to gain access to autism-related services is known to be a major burden. These challenges to service access are compounded for newcomers to Canada, which include immigrants and refugees. The purpose of this scoping review is to describe the available research on Canadian newcomer caregiver experiences navigating and accessing autism-related services. After a systematic search and screening process, 28 studies were included. Data were extracted regarding the populations, study aims, and themes reported. Included studies characterized barriers and facilitators to service access and navigation specific to immigrants, while limited information was available for refugees. Based on the existing literature, the authors provide recommendations for possible research approaches, populations to include, and themes to examine in future research to promote health equity in Canadian autism service access.